Leveraging community health workers as vaccinators: a case study exploring the role of Malawi's Health Surveillance Assistants in delivering routine immunization services - Rebecca Alban; Emily Gibson; Jenny Payne; Tafwirapo Chihana (BMC, 2023)
Abstract Background Global chronic health worker shortages and stagnating routine immunization rates require new strategies to increase vaccination coverage and equity. As trained, trusted members of their local communities, community health workers (CHWs) are in a prime position to expand the immunization workforce and increase vaccination coverage in under-reached communities. Malawi is one of only a few countries that relies on CHWs-called Health Surveillance Assistants (HSAs) in Malawi-to administer routine immunizations, and as such offers a unique example of how this can be done. Case presentation We sought to describe the operational and programmatic characteristics of a functional CHW-led routine immunization program by conducting interviews with HSAs, HSA supervisors, ministry of health officials, and community members in Malawi. This case study describes how and where HSAs provide vaccinations, their vaccination-related responsibilities, training and supervision processes, vaccine safety considerations, and the community-level vaccine supply chain. Interview participants consistently described HSAs as a high-functioning vaccination cadre, skilled and dedicated to increasing vaccine access for children. They also noted a need to strengthen some aspects of professional support for HSAs, particularly related to training, supervision, and supply chain processes. Interviewees agreed that other countries should consider following Malawi's example and use CHWs to administer vaccines, provided they can be sufficiently trained and supported. Conclusions This account from Malawi provides an example of how a CHW-led vaccination program operates. Leveraging CHWs as vaccinators is a promising yet under-explored task-shifting approach that shows potential to help countries maximize their health workforce, increase vaccination coverage and reach more zero-dose children. However, more research is needed to produce evidence on the impact of leveraging CHWs as vaccinators on patient safety, immunization coverage/vaccine equity, and cost-effectiveness as compared to use of other cadres for routine immunization.